Mid-Infrared Polycyclic Aromatic Hydrocarbon and H2 Emission as a Probe of Physical Conditions in Extreme Photodissociation Regions - Berné, O; Fuente, A; Goicoechea, J. R; Pilleri, P; González-García, M; Joblin, C (Astrophysical journal. Letters, 2009)
Mid-infrared (mid-IR) observations of polycyclic aromatic hydrocarbons (PAHs) and molecular hydrogen emission are a potentially powerful tool to derive physical properties of dense environments irradiated by intense UV fields. We present new, spatially resolved, Spitzer mid-IR spectroscopy of the high UV field and dense photodissociation region (PDR) around Monoceros R2, the closest ultracompact H II region, revealing the spatial structure of ionized gas, PAHs, and H2 emissions. Using a PDR model and PAH emission feature fitting algorithm, we build a comprehensive picture of the physical conditions prevailing in the region. We show that the combination of the measurement of PAH ionization fraction and of the ratio between the H2 0-0 S(3) and S(2) line intensities, respectively, at 9.7 and 12.3 Delta *mm, allows us to derive the fundamental parameters driving the PDR: temperature, density, and UV radiation field when they fall in the ranges T = 250-1500 K, n H = 104-106 cm-3, and G 0 = 103-105, respectively. These mid-IR spectral tracers thus provide a tool to probe the similar but unresolved UV-illuminated surface of protoplanetary disks or the nuclei of starburst galaxies.